2022
DOI: 10.1093/nar/gkac184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for human mitochondrial tRNA m3C modification by alternatively spliced METTL8

Abstract: METTL8 has recently been identified as the methyltransferase catalyzing 3-methylcytidine biogenesis at position 32 (m3C32) of mitochondrial tRNAs. METTL8 also potentially participates in mRNA methylation and R-loop biogenesis. How METTL8 plays multiple roles in distinct cell compartments and catalyzes mitochondrial tRNA m3C formation remain unclear. Here, we discovered that alternative mRNA splicing generated several isoforms of METTL8. One isoform (METTL8-Iso1) was targeted to mitochondria via an N-terminal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…We have successfully purified mature SARS2 from E. coli ( 32 , 33 ). We obtained mature forms of wild-type, Ins12, and dupC, and then performed thermal shift assays (TSA) to determine the stability of purified proteins in vitro ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have successfully purified mature SARS2 from E. coli ( 32 , 33 ). We obtained mature forms of wild-type, Ins12, and dupC, and then performed thermal shift assays (TSA) to determine the stability of purified proteins in vitro ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…A construct expressing the full-length mature form of SARS2 with a C-terminal His 6 -tag was developed according to a previous report ( 33 ). Constructs expressing Ins12 and dupC were generated using mutagenesis kits (TOYOBO, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…For ac4C, writers included NAT10 and THUMPD1; and erasers and readers remain unknown ( 18 , 19 ). For m3C, only one writer METTL8 was discovered, and erasers and readers were still undetected ( 20 ). For m6Am, writers included PCIF1, METTL3, and METTL4; eraser involved FTO; and no readers were discovered ( 21 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…METTL6 interacts with seryl-tRNA synthetase (SerRS, encoded by SARS1) to mediate the biogenesis of m3C32 modification in human tRNA Ser [ 9 ]. In contrast to the preceding three cytoplasmic m3C32-modifying enzymes, it had been established that METTL8 functioned in mitochondria [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The m3C32 modification of mitochondria tRNA Ser and tRNA Thr were catalyzed by the mitochondrial protein METTL8 and the high expression of METTL8 contributed an enhanced respiratory chain activity in pancreatic cancer [ 10 ]. The alternative mRNA splicing research reported that one of the isoforms of METTL8, METLL8-iso1, had been investigated to be transported to mitochondrial with the assistance of its N-terminal mitochondrial targeting sequence [ 11 ]. Aside from the classical m3C32 modification of mitochondrial tRNAs, upregulated of METTL8 by Yin Yang 1 (YY1) transcription factor mediated the m3C modification on the mRNA of AT-rich interactive domain-containing protein 1A and attenuated its translation, which induced the migration of breast cancer cell lines [ 17 ].…”
Section: Introductionmentioning
confidence: 99%